ANALISIS KEPUASAN PELANGGAN TERHADAP LAYANAN PURNA JUAL AVANZA DENGAN METODE SERVQUAL DAN PGCV (Studi Kasus BPPT HADJI KALLA CABANG URIP MAKASSAR) - Darmawan, Armin; Mulyadi, Mulyadi; Busri, Nur Khaerani (JEMIS (Journal of Engineering & Management in Industrial System), 2014)
This research examine cutomer level of satisfaction at service and repair in Toyota Hadji Kalla that aim to determine attributes which are priorities at PGCV index analysis. Method used in this study is servqual. This method is a tool used to measure quality of service attribute of each dimension (tangible, reliability, responseiveness, emphaty, and assurance). So we get the value of gap from different value between perception and expectation in customer value. This research followedÂ  by Potential Gain Customer Value (PGCV) method. Based on the survey results , the overall value of the average interest rate is 4.435 and the average value of the performance level is 3.924 , which means there is a gap between the service desired by the customer service received by 0.511 . By using PGCV index priority improvements to enhance the level of customer satisfaction is the availability of the quantity of automobile parts and components that meet the needs of customers , employees BPPT HK able to meet the delivery schedule of the vehicle as promised schedule , as well as employees of HK BPPT has properties polite , friendly , honest , and trustworthy.